Factors Influencing Job Satisfaction among Nurses in Public Health Facilities in Mombasa, Kwale and Kilifi Counties, Kenya - Tengah, Soud Alli; Otieno, Ogembo John (Advances in Social Sciences Research Journal, 2019)
The study sought to establish factors that influence job satisfaction of nurses in Kenya. This was necessitated by the need to contribute in bridging existing knowledge gap with regard to predictors of Nurses’ job satisfaction. Whereas job satisfaction has been shown to influence nurse retention in employment, turnover rates and provision of quality patient care, job satisfaction of nurses has received minimal attention in Kenya. In Kenya, nurses who constitute the largest cadre of health care providers especially in public health facilities and contribute significantly in the health care system earn low salaries, work in poor working conditions and experience huge nurse to patient imbalance ratio. While these factors among others could have an impact on their morale and ultimately productivity, data on the effect the factors on nurses’ job satisfaction is non-existent. This study therefore sought to explore the extent to which demographic factors; perceived leader empowering behaviour; work environment and job stress predict job satisfaction among nurses working in public hospitals within the country. Data was collected using structured questionnaire to 142 nurses in public hospitals in Mombasa, Kwale and Kilifi counties. Findings illustrated that nurses’ age, time, work load and reward contribute significantly towards nurses’ job satisfaction. Other contributing factors were nurse physician relationship and personnel. It is therefore recommended that concerted efforts be put in place to improve the quality of leadership to inspire nurses and thus enhance their job satisfaction, an aspect that is currently missing.